Techniques Used in Forensic Psychological Examinations in Cases of Child and Adolescent Sexual Abuse - Gava, Lara Lages; DellAglio, Debora Dalbosco (Paidéia (Ribeirão Preto), 2013)
Currently, there is no standardized protocol for the evaluation of situations of sexual abuse. Thus, this study investigated the techniques used by psychologists in forensic examinations in cases of suspected child and adolescent sexual abuse in the context of the criminal investigation. Semi-structured interviews, which were qualitatively analyzed using the WebQDA software, were applied with twelve psychologists who work as expert witnesses in the Medical-Legal Institute of six Brazilian capitals. The results showed a diversity of actions taken in the forensic examination practice, as well as consensus and controversy regarding the use of psychological testing and the credibility assessment of the report. Flexibility in conducting the forensic examinations by the teams was also observed, with the techniques used adapted according to the needs. The importance of the diversity of techniques was highlighted, as these aim to assist the expert witness to come to reliable conclusions, as well as maintain the rigor and technical quality of the evaluation.